Optimal multimedia combination for students with dyslexia - Lebeničnik, Maja (Metodološki zvezki, 2020)
Many contemporary online learning resources use more than one sensory modality (audio, visual) or presentation mode (pictures, text). Multimedia learning material is often recommended for and adopted by students with dyslexia. However, there are not many empirical studies that support the benefits of multimedia for this group. Due to the variety of difficulties that these students may experience, multimedia may not be the most appropriate type of online content for them. Our study aimed to identify the most appropriate combination of multimedia content for them from among three commonly-used types of online learning resources. An experiment was conducted in which 27 students with dyslexia learned about a topic under one of three conditions: a scroll-down website with onscreen text and static pictures, video lecture and subtitled video lecture. No significant differences in learning outcomes were found between the groups. However, the effect sizes indicated the superiority of the website over the other two conditions. Because of the small sample size, further research is needed.
Keywords: accessibility; cognitive theory of multimedia learning; disleksija; dostopnost; dyslexia; kognitivna teorija multimodalnega učenja; video